Memory Integration as a Challenge to the Consolidation/Reconsolidation Hypothesis: Similarities, Differences and Perspectives - Gisquet-Verrier, Pascale; Riccio, David C. (Frontiers in Systems Neuroscience, 2019)
We recently proposed that retrograde amnesia does not result from a disruption of the consolidation/reconsolidation processes but rather to the integration of the internal state induced by the amnesic treatment within the initial memory. Accordingly, the performance disruption induced by an amnesic agent does not result from a disruption of the memory fixation process, but from a difference in the internal state present during the learning phase (or reactivation) and at the later retention test: a case of state-dependency. In the present paper, we will review similarities and differences these two competing views may have on memory processing. We will also consider the consequences the integration concept may have on the way memory is built, maintained and retrieved, as well as future research perspectives that such a new view may generate.